Multimorbidity in General and Family Medicine: Construction and Validation of the Questionnaire of Evaluation of Burden of Management of Multimorbidity in General and Family Medicine: Multimorbilidade em Medicina Geral e Familiar: Construção e Validação do Questionário de Avaliação da Sobrecarga da Gestão da Multimorbilidade em Medicina Geral e Familiar (SoGeMM-MGF) - Prazeres, Filipe; Santiago, Luiz Miguel; Pereira, Pedro Miguel; Santos, Pedro Miguel; Cortinhal, Telmo (Gazeta Médica, 2019)
INTRODUCTION: The management of multimorbidity can lead to medical burden that should be evaluated. Our objective was to create and validate a questionnaire to measure the burden of the management of multimorbidity in Family Physicians. MATERIAL AND METHODS: The questionnaire was constructed after a literature review on multimorbidity and information from a focus group. The construct validity was performed using the maximum likelihood method for factor analysis, followed by simple oblique rotation (oblimin), in a sample of family physicians after a pre-test. RESULTS: Validation of the study of 223 family physicians’ responses (120 women), mean age of 51.4 ± 13.1 years, from the centre of Portugal, through an invitation to complete the online questionnaire. After the analysis, the questionnaire was reduced from 23 to 16 items, showing good internal consistency and construct validity, with four factors explaining 66.6% of the total variance of the questionnaire. Cronbach’s alpha, for the global scale of 0.89 and factors between 0.88X and 0.49Y. DISCUSSION: SoGeMM-MGF with 16 questions allows to evaluate 4 areas of impact of multimorbidity. This tool clarifies areas and difficulties experienced by medical professionals and may guide the development of solutions for a more effective management of multimorbidity. Despite the good psychometric properties of the questionnaire, in the future more robust studies of its concurrent and discriminative validity and temporal stability in larger samples and in other areas of the country will be necessary. CONCLUSION: The questionnaire can be considered a reliable instrument for assessing the burden of multimorbidity management in general and family medicine.